Perubahan Perilaku Siswa dalam Pembelajaran Tatap Muka di Kelas Pascapandemi : Potret Pembelajaran di Awal Era Merdeka Belajar - Agus Purnomo Ahmad Putikadyanto; Liana Rochmatul Wachidah; Ilmi Firdaus Aliyah; Sri Helda Herawati; Miftahul Abrori (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
About all educational levels have started offering offline sessions lately, nearly two years after beginning home-study or hybrid classes. When students return to in-person learning at school, there are signs of behavioral changes. This study set out to describe how student behavior changed in terms of knowledge, attitudes, and skills during face-to-face instruction during the post-pandemic. This study employed a quantitative methodology to address this question by distributing questionnaires to students in elementary, middle, and high schools in the cities of Pamekasan and Mojokerto. For the goal of triangulation, interviews with teachers were also performed in 11 provinces in western Indonesia. s a result, there were both positive and negative behavioral changes among elementary, middle, and high school students. To improve learning, teachers, parents, and students themselves must be able to recognize changes in post-pandemic student behavior. Though it can certainly facilitate human endeavors, teachers' roles as educators have not yet been fully replaced by technology, at least not yet.